Suplement. Abstract. III International Congress of AEPROMO (Ozone Therapy Global Journal, 2012)
The 3rd. International Congress of AEPROMO “Ozone therapy in the medical agenda” is a great new step forward, the many that our association has been giving in favor of ozone therapy. After the creation of AEPROMO in 2008, we launched the first international congress in 2009. This had a significant impact because we did it after the Madrid Community lifted the prohibition against the practice of ozone therapy in outpatient centers. He also authorized his practice and detailed in writing the requirements so that it could be carried out. The 2009 congress of Pontevedra marked an important milestone for three reasons: Ozone therapy in Spain began to be regulated by the health authorities; For the first time a congress of ozone therapy received the title of “Sanitary Interest”; And finally because we managed to convene important personalities from the world of ozone therapy in Pontevedra to share experiences and transmit knowledge.